HINTW, a W‐chromosome HINT gene in chick, is expressed ubiquitously and is a robust female cell marker applicable in intraspecific chimera studies. Issue 5 (13th March 2014) - Nagai, Hiroki; Sezaki, Maiko; Bertocchini, Federica; Fukuda, Kimiko; Sheng, Guojun
Abstract Grafting and transplantation experiments in embryology require proper distinction between host and donor tissues. For the avian model this has traditionally been achieved by using two closely related species (e.g., chick and quail) followed by species‐specific antibody staining. Here, we show that an in situ hybridization probe against the HINTW gene is a robust and reliable marker for female‐derived chicken cells. At all pre‐circulation stages tested, all cells in female embryos, independently confirmed by PCR analysis, were strongly positive for HINTW, whereas all male embryos were negative. This probe is broadly applicable in intra‐specific chick/chick chimera studies, and as a proof of principle, we utilized this probe to detect female cells in three experimental settings: (1) to mark female donor cells in a node transplantation assay; (2) to distinguish female cells in male/female twins generated by the Cornish pasty culture; and (3) to detect female half of the embryo in artificially generated bilateral gynandromorphs. A rapid, PCR based pre‐screening step increases the efficiency of obtaining desired donor/host sex combination from 25% to 100%. For most avian chimera studies, this female‐specific in situ probe is a low cost alternative to the commonly used QCPN antibody and to ubiquitous‐GFP chicken strains which are not widely available to the research community. genesis 52:424–430, 2014. © 2014 Wiley Periodicals, Inc.